PENGARUH GADGET TERHADAP PERKEMBANGAN PSIKOLOGIS BAGI ANAK USIA DINI - Rr. Dina Kusuma Wardhani (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2016)
Communication tools getting bolder lively variety of shapes, types and all means of communication have advantages of each. The more unique, more sophisticated with a wide range of applications in its sure to be a choice many circles without exception. The gadget is one of the communication tools that are familiar to those of us living in urban areas. Via Gadget looks like someone will be entertained with a variety of applications in it. But behind the entertainment Gadget meyimpan any information that can be positive if it is used wisely and can be negative if used without any clear time restrictions especially for early childhood.